Cultured Meat for Indonesian Muslim Communities: A Review of Maslahah and Prospect - Qotadah, Hudzaifah Achmad; Al Anshory, Ali Chamani; Achmad, Adang Darmawan; Syarifah, Ma’isyatusy (Institut Agama Islam Negeri Curup, 2022)
The aim of this study is to examine the concerns surrounding cultured meat and the obstacles it presents in terms of halal issues, particularly for Muslim communities in Indonesia. The production of cultured meat is currently being heralded as one of the most significant advances of this century. Cultured meat is something that is made in a lab using techniques from bioengineering. Although it is not raised on farms like traditional meat, it shares many of the same biological similarities. This innovation still confronts several obstacles, such as the halal issue, which is still discussed by many Muslim academics, including those in Indonesia. A full qualitative method was employed, which was based on library research to investigate the stated problems, and all the findings were analyzed descriptively. The findings of the study have revealed that, despite various different arguments from Muslim academics’ perspectives regarding the halal status of cultured meat, it will be wiser if the related authorities as well as religious institutions join forces to examine the halal status of cultured meat. Once cultured meat is recognized as halal, it will provide more significant benefits, particularly for Muslim communities in Indonesia. It is also taken into consideration that cultured meat may have the ability to overcome global problems associated with the environmental implications of meat production, animal welfare, food security, as well as human health, or in other words it can offer certain mashlahah in comparison to traditional meat production.